Synthetic studies of cystobactamids as antibiotics and bacterial imaging carriers lead to compounds with high in vivo efficacy. Issue 5 (20th December 2019) - Testolin, Giambattista; Cirnski, Katarina; Rox, Katharina; Prochnow, Hans; Fetz, Verena; Grandclaudon, Charlotte; Mollner, Tim; Baiyoumy, Alain; Ritter, Antje; Leitner, Christian; Krull, Jana; van den Heuvel, Joop; et al.
Abstract : Structure–activity relationship studies of the natural product cystobactamid at four different positions led to novel imaging probes and analogs with superior antibacterial activities and in vivo efficacy. Abstract : There is an alarming scarcity of novel chemical matter with bioactivity against multidrug-resistant Gram-negative bacterial pathogens. Cystobactamids, recently discovered natural products from myxobacteria, are an exception to this trend. Their unusual chemical structure, composed of oligomeric para -aminobenzoic acid moieties, is associated with a high antibiotic activity through the inhibition of gyrase. In this study, structural determinants of cystobactamid's antibacterial potency were defined at five positions, which were varied using three different synthetic routes to the cystobactamid scaffold. The potency against Acinetobacter baumannii could be increased ten-fold to an MIC (minimum inhibitory concentration) of 0.06 μg mL −1, and the previously identified spectrum gap of Klebsiella pneumoniae could be closed compared to the natural products (MIC of 0.5 μg mL −1 ). Proteolytic degradation of cystobactamids by the resistance factor AlbD was prevented by an amide-triazole replacement. Conjugation of cystobactamid's N-terminal tetrapeptide to a Bodipy moiety induced the selective localization of the fluorophore for bacterial imaging purposes. Finally, a first in vivo proof of concept was obtained in an E. coli infection mouse model, where derivative 22 led to the reduction of bacterial loads (cfu, colony-forming units) in muscle, lung and kidneys by five orders of magnitude compared to vehicle-treated mice. These findings qualify cystobactamids as highly promising lead structures against infections caused by Gram-positive and Gram-negative bacterial pathogens.